Mouse Models of Age-related Mitochondrial Neurosensory Hearing Loss - Han, Chul (2012)
Hearing loss is the most common sensory disorder in the elderly population. Overall, 10% of the population has a hearing loss in the US, and this age-related hearing disorder is projected to afflict more than 28 million Americans by 2030. Age-related hearing loss is associated with loss of sensory hair cells (sensory hearing loss) and/or spiral ganglion neurons (neuronal hearing loss) in the cochlea of the inner ear. Many lines of evidence indicate that oxidative stress and associated mitochondrial dysfunction play a central role in age-related neurodegenerative diseases and are a cause of age-related neurosensory hearing loss. Yet, the molecular mechanisms of how oxidative stress and/or mitochondrial dysfunction lead to hearing loss during aging remain unclear, and currently there is no treatment for this age-dependent disorder. Several mouse models of aging and age-related diseases have been linked to age-related mitochondrial neurosensory hearing loss. Evaluation of these animal models has offered basic knowledge of the mechanism underlying hearing loss associated with oxidative stress, mitochondrial dysfunction, and aging. Here we review the evidence that specific mutations in the mitochondrial DNA or nuclear DNA that affect mitochondrial function result in increased oxidative damage and associated loss of sensory hair cells and/or spiral ganglion neurons in the cochlea during aging, thereby causing hearing loss in these mouse models. Future studies comparing these models will provide further insight into fundamental knowledge about the disordered process of hearing and treatments to improve the lives of individuals with communication disorders.